The effect of a 3-week training block on physiological responses and performance in elite kayakers - Paquette, M.; Bieuzen, F.; Billaut, F. (Applied Physiology, Nutrition, and Metabolism, 2018)
Muscle O2 extraction in the latissimus dorsi (LD) and vastus lateralis (VL) have recently been shown to be better predictors of performance thanVO2max in sprint kayak, but the effect of training on these indicators has not been investigated. This study examined the changes in muscle oxygenation (SmO2, % of baseline), VO2max and performance following a 3-week training block. Seven elite kayakers from the Canadian National Team completed a 1000-m time trial (TT) before and after the 3-week training block. O2 consumption (Cosmed K5), post-race blood lactate and SmO2 (Moxy monitors) in the LD, biceps brachii (BB), and VL were measured during the TT. Training load was measured in 3 athletes using heart rate (HR) monitors. Athletes trained for 58±1 hours and spent 35±5%, 33±6%, 20±6%, 9±1% and 3±2% of training time in zones 1 to 5 during the 3-week training block. 1000-m TT performance improved by 3±2% (3:54±0:06 to 3:46±0:02, ES:1.5[0.9,2.1]) concomitant with a moderate increase in VO2 max (5.3±0.4 to 5.5±0.3 L/min, ES: 0.6[0.1,1.1]) and a moderate decrease in blood lactate concentration (11.8±1.8 to 10.5±2.8 mmol, ES:-0.6[-0.1,-1.1]). There was a greater deoxygenation in BB after the training block (60±7 to 54±4%, ES:-1.0[-1.6,-0.5]) but it was inversely related with changes in performance (R=0.6). VL SmO2 did not change with training (66±30 to 66±5%). A traditional 3-week training block leads to a large improvement in performance and an increase in VO2max and aerobic contribution, but was ineffective to improve VL O2 extraction. A more concentrated training load, specifically targeting peripheral adaptations, might be necessary to improve muscle O2 extraction capacity and may further enhance performance in kayak.